Evaluations of Co-Cr-Mo meta-biomaterial manufactured by selective laser melting for orthopaedic application - Siti Rohaida, Mohamed; S. A., Che Ghani; W. S., Wan Harun; Nor Aida Zuraimi, Md Noar (2016)
Meta-biomaterial with rationally design geometrical features provides an exciting opportunity to reduce stress shielding effect and enhance biological fixation as vital criteria for longer durability load-bearing implants. Recently, selective laser melting (SLM), an additive manufacturing has shown significant advantages to produce complex shape which component’s dimensions are close to final dimensions with high degree of interconnected structure. Nonetheless, the available data on achievable accuracy of parts with different geometries from this manufacturing process is scarce. In this study, meta-biomaterials with two different unit cells types made of cobalt chrome molybdenum (Co-Cr-Mo) namely square and diamond are designed with varied unit cell length, Lcell of 1.5 mm and 2.5 mm while strut size, ΦS of 0.4 mm and 0.6 mm then fabricated by SLM. The effects of unit cell geometries on the manufacturability and density were investigated. The manufacturability accuracy has a good geometric agreement between fabricated samples and original computer aid designed models (CAD). The optical microscope images reveal the partially melted metal particles are bonded to the strut surface. The structures with bigger strut size have higher density due to denser struts.